A cross-cultural investigation of people’s intuitive beliefs about the origins of cognition - Meng, Xianwei; Wang, Jinjing Jenny; Yoshikawa, Yuichiro; Ishiguro, Hiroshi; Itakura, Shoji (Frontiers in Psychology, 2022)
Nature vs. nurture is an enduring theme of studies of the mind. Past studies on American children and adults have revealed a preference for thinking that even fundamental cognitive abilities documented in human infants and non-human species are late-emerging and reliant on learning and nurture. However, little is known about the generalizability of this “intuitive empiricist” belief and what factors may help explain it. Adult participants (N = 600) reported their beliefs about the emergence of several fundamental cognitive abilities demonstrated by preverbal infants. Studies 1A-1C showed that adults from both Japan and the US similarly estimated an older age of onset for cognitive abilities in human children as compared to the findings of cognitive science and consistently attributed acquisition of these abilities to learning rather than innateness in humans, and they made these learning attributions more so for humans than for non-human species. Study 2 showed that participants’ beliefs about biological evolution versus creationism were related to their age onset estimates for fundamental cognitive abilities, and their beliefs about the malleability of intelligence were related to participants’ explanations of the origin of fundamental cognitive abilities. These findings suggest generalizable preferences for nurture over nature across both Eastern and Western cultures (Japan and the United States), which may be related to people’s beliefs about human origins and the power of learning.